The Four-Step Model Approach for Improving Public Transportation in Malang City - Alrasyid, Putri Amelya; Andaru, Nindya Miatani; Nurrizkyta , Ditha (Jurnal Indonesia Sosial Sains, 2025)
Malang City, which is directed as a National Activity Center (NAC) as well as a center for education and trade and services, certainly faces major challenges in transportation management due to significant population, student and tourist growth. With a population of 847,182 people in 2023 and the dominance of private vehicle use, the city is ranked as the fourth most congested city in Indonesia based on the Global Traffic Scorecard in 2021. This article aims to provide recommendations for improving public transportation in Malang City using the Four-Step Model approach, which consists of trip generation, trip distribution, mode choice, and trip assignment stages. Each stage of the model is used to identify movement patterns, transportation mode preferences, and optimal travel routes. The data used is secondary data obtained from the Malang City Transportation System Planning Report (Itenas , 2020). The results show that Lowokwaru, Klojen, and Sukun sub-districts have the highest movement rates. The dominant educational, trade and service and residential activities in these areas generate a lot of movement to and from other sub-districts. In addition, mode choice analysis shows that the use of modes is dominated by private vehicles at 96% while public transportation is only 4%. Recommendations based on these findings include the expansion of public transport routes, fleet modernization, restrictions on private vehicles, and the development of electronic payment systems. The findings are expected to serve as a foundation for integrated and sustainable transportation planning for Malang City.